A survey to assess the female sexual harassment in the higher educational institutes of Karachi, Pakistan / Zulfiqar Ali Shaikh, Muhammad Zaman Shaikh and Masood Hameed Khan - Shaikh, Zulfiqar Ali; Shaikh, Muhammad Zaman; Hameed Khan, Masood (Division of Research and Industry Linkages, UiTM Melaka, 2014)
Objectives: To determine the nature and frequency of the exposure of female students to sexual harassment at higher educational institutes and explore the adverse effects of sexual harassment on the victims and coping strategies implied by them. Background: Sexual harassment, whether at workplace, educational institution, street, or leisure, is a problem gaining increasing recognition in every society. Despite widespread nature of the problem, there are still considerable misunderstandings as well as differences of opinion concerning whether particular situations or behaviors are sexually harassing in nature or not. The victim may feel threatened, humiliated, and harassed, and this would interfere with the performance, satisfaction, and commitment and undermine security or create an intimidating environment. Subjects and Method: A total 480 female students were conveniently selected from ten different educational institutes and were provided a self-administered questionnaire with their consent. The identity of all the study subjects was kept secret. The study was conducted from January 6 to September 30, 2009. The data were analyzed by using SPSS version 15. Results: Out of 480 female students, 460, i.e., 96 %, returned the filled questionnaires. Among them, 65 % reported of sexual harassment of various degrees/levels irrespective of their residential area, appearance, and attire. These females were harassed by the fellow students (37 %), faculty (32 %), and strangers (64 %) who included patients, attendants, visitors, and passersby. Although almost all of the participants (98 %) wanted a punishment for the harassers, they (78 %) were reluctant to disclose the name/identity of those perpetrators because of the fear of exploitation, social taboo, further embarrassment, adverse consequences, and career obstacles. Conclusion: Many females were the victim of sexual harassment in various forms. There is a need to sensitize the society, and mass awareness programs should be carried out through variety of media.